2019
DOI: 10.1186/s12875-019-0983-y
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to screening and treating malnutrition in older adults living in the community: a mixed-methods synthesis

Abstract: Background Malnutrition (specifically undernutrition) in older, community-dwelling adults reduces well-being and predisposes to disease. Implementation of screen-and-treat policies could help to systematically detect and treat at-risk and malnourished patients. We aimed to identify barriers and facilitators to implementing malnutrition screen and treat policies in primary/community care, which barriers have been addressed and which facilitators have been successfully incorporated in existing inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 56 publications
(91 reference statements)
2
36
0
7
Order By: Relevance
“…The topic guide was based on evidence and evidence gaps, including findings from a mixed‐methods review ( 21 ) and previous qualitative research, as discussed in the Introduction. There were seven key questions, each with ‘probing’ questions that interviewers could use to prompt further detail about topics of interest, if needed.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The topic guide was based on evidence and evidence gaps, including findings from a mixed‐methods review ( 21 ) and previous qualitative research, as discussed in the Introduction. There were seven key questions, each with ‘probing’ questions that interviewers could use to prompt further detail about topics of interest, if needed.…”
Section: Methodsmentioning
confidence: 99%
“…A range of physical and psychosocial factors can undermine motivation to improve eating habits ( 20 ) by promoting unhelpful beliefs and fears. A mixed‐methods review identified that patients had reservations about screening and discussing diet ( 21 ) , and that difficulty chewing, swallowing, shopping or preparing food are barriers to nutritional self‐care ( 21 ) . Psychosocial barriers included not considering nutrition important, not recognising personal risk, avoiding ‘unhealthy’ energy‐dense food and loneliness ( 21 ) , being told to gain weight and not believing that recommendations will work ( 22 ) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the individual-level contributors to and consequences of malnutrition are known and important (as referenced above), less is known about the communitylevel influences on malnutrition death among older adults ( 22 ). An abundance of available studies about malnutrition examine school-aged youth ( 23 – 25 ); however, when older adults are specifically examined, studies typically target individual-level variables among mostly community-dwelling older adults ( 26 ). Unfortunately, such studies do not consider the totality of the aging population in a particular geographic area within the context of available resources young AND MIDDLE AGED ADULTS residents residing in the same geographic area.…”
Section: Introductionmentioning
confidence: 99%